Effect of Compounds Affecting ABCA1 Expression and CETP Activity on the HDL Pathway Involved in Intestinal Absorption of Lutein and Zeaxanthin. Issue 12 (10th October 2014) - Niesor, Eric J.; Chaput, Evelyne; Mary, Jean‐Luc; Staempfli, Andreas; Topp, Andreas; Stauffer, Andrea; Wang, Haiyan; Durrwell, Alexandre
Abstract: The antioxidant xanthophylls lutein and zeaxanthin are absorbed from the diet in a process involving lipoprotein formation. Selective mechanisms exist for their intestinal uptake and tissue‐selective distribution, but these are poorly understood. We investigated the role of high‐density lipoprotein (HDL), apolipoprotein (apo) A1 and ATP‐binding cassette transporter (ABC) A1 in intestinal uptake of lutein in a human polarized intestinal cell culture and a hamster model. Animals received dietary lutein and zeaxanthin and either a liver X receptor (LXR) agonist or statin, which up‐ or down‐regulate intestinal ABCA1 expression, respectively. The role of HDL was studied following treatment with the cholesteryl ester transfer protein (CETP) modulator dalcetrapib or the CETP inhibitor anacetrapib. In vitro, intestinal ABCA1 at the basolateral surface of enterocytes transferred lutein and zeaxanthin to apoA1, not to mature HDL. In hamsters, plasma lutein and zeaxanthin levels were markedly increased with the LXR agonist and decreased with simvastatin. Dalcetrapib, but not anacetrapib, increased plasma and liver lutein and zeaxanthin levels. ABCA1 expression and apoA1 acceptor activity are important initial steps in intestinal uptake and maintenance of lutein and zeaxanthin levels by an HDL‐dependent pathway. Their absorption may be improved by physiological and pharmacological interventions affecting HDL metabolism.